GAMBARAN RESILIENSI PADA ORANG TUA YANG MENGALAMI EMPTY NEST SYNDROME - Handoyo, Christina Irene Dwi; Agustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tarumanagara, 2023)
This research was conducted with the aim of finding out what resilience looks like in parents who experience empty nest syndrome. There were 80 participants who met the research criteria, namely parents in the middle adult age range of 40-60 years who no longer lived with their children. Data collection in this research was carried out using snowball sampling by asking participants for help in inviting colleagues who met the research criteria to become participants. The measuring instruments used in this research were the Resilience Scale (RS-14) and the Empty Nest Syndrome Scale-Indian Form (ENS-IF). The results of the descriptive analysis showed that there were 13 participants with a low level of resilience, 54 participants with a medium level of resilience and 13 participants with a high level of resilience.